Presenting an Ideal Self on Weibo: The Effects of Narcissism and Self-Presentation Valence on Uses and Gratifications - Huang, Lei Vincent; Liu, Susu (Frontiers in Psychology, 2020)
Narcissism has been shown to have a positive and significant impact on uses of microblog services and features for self-presentation. Little is known with regard to whether and how narcissism and valence of online self-presentation could jointly influence the gratifications of microblog uses. This study explores how narcissism influences the uses and gratifications of Weibo via positive and negative self-presentation. Results from a survey of Weibo users in China suggest that narcissism generates positive effect on both gratification sought and gratification obtained. Gratification sought fully mediates the effect of narcissism on gratification obtained. Moreover, positive self-presentation plays a mediating role between gratification sought and gratification obtained, while negative self-presentation does not. The mediation mechanisms within narcissism, the valence of self-presentation, gratification sought, and gratification obtained suggests that differentiating the gratification processes could help us better understand mechanisms in uses and gratification of microblog services.